Effects of rain on scintillation measured on Ku-Band Satellite Signals in tropical region - Nadirah , Abdul Rahim; Islam, Md. Rafiqul; J.S, Mandeep; Hassan , Dao (2012)
Analysis of the tropospheric scintillation from earth to space at Ku-band has been carried out in order to obtain the required cut off frequency for the scintillation. This paper presents a comparison of scintillation amplitude and scintillation intensity between rain and non-rain event using data measured in Kuala Lumpur in December 2011. The findings denote that the signal level of scintillation during rain is higher than during non-rain event. The findings also demonstrate that as the elevation angle is higher, the path length will be smaller. Therefore, the scintillation amplitude will be small.